Antecedents of environmental performance of front-line managers in hospitality industry of Pakistan - Muhammad Tariq; Muhammad Yasir; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This study is an attempt to find out the effect of line managers' environmental attitude on their organizational citizenship behavior for environment (OCBE) and environmental performance (EP). In addition to above examination, the study has also made an investigation regarding the mediating role of OCBE in the relationship of management environmental awareness (MEA) and managers' environmental performance (MEP). Moderating effect of top management awareness for environment has also been tested on the link between MEA and OCBE. Data for this study was collected from 546 front line managers from 154 hotels and tourism units operating in Pakistan. Data analysis was carried out through correlation, linear regression as well structural equation modeling (SEM). Results of the study reported a direct effect of MEA on OCBE and MEP. Moreover, the findings validate that OCBE mediates between MEA and MEP. Furthermore, the findings confirmed that top management environmental awareness (TMEA) supports the link between MEA and OCBE. This study provides novel insights for environmental performance of hospitality industry of Pakistan by emphasizing the environmental attitude, OCBE and MEA. Thus it advocates new mechanisms that would be supportive in initiating protection of natural environment. Study provides significant insight to literature by contributing new knowledge regarding the positive associations of manager's environmental attitude and OCBE in the context of hospitality industry of Pakistan.
Keywords: 330; manager environmental attitude; organizational citizenship behavior for environment; manager environmental performance; management environmental awareness; front line managers; hospitality industry